Madrasah Ibtidaiyah 4.0 - sari, devit etika (STAI Miftahul Ula Nganjuk, 2024)
This study examines the integration of Madrasah Ibtidaiyah 4.0, an educational model utilizing advanced technology to foster religious moderation in Indonesian Islamic primary schools. The research focuses on three Madrasah Ibtidaiyah (MI Al-Barokah, MI Darul Muta’allimin, and MI Nurussalam), chosen for their diverse geographical contexts (urban, border, and rural) and varying levels of technological infrastructure. The study includes 5 teachers, 3 principals, and 60 students from these schools as the primary research subjects. It explores how digital platforms, mobile applications, and online learning environments are used to teach Islamic values, with a focus on pluralism, tolerance, and anti-radicalism. Findings show that technology significantly enhances student engagement and understanding of Islamic teachings, providing opportunities for a moderate worldview. However, the study also identifies key challenges such as inadequate infrastructure, limited access to technology, and the need for teacher training. The study concludes that when implemented effectively, technology can be a powerful tool in promoting moderate religious values and creating an inclusive, balanced approach to Islamic education.